Genomic Regions Associated With Seed Meal Quality Traits in Brassica napus Germplasm - Bhinder, Gurleen; Sharma, Sanjula; Kaur, Harjeevan; Akhatar, Javed; Mittal, Meenakshi; Sandhu, Surinder (Frontiers in Plant Science, 2022)
The defatted Brassica napus (rapeseed) meal can be high-protein feed for livestock as the protein value of rapeseed meal is higher than that of the majority of other vegetable proteins. Extensive work has already been carried out on developing canola rapeseed where the focus was on reducing erucic acid and glucosinolate content, with little consideration to other antinutritional factors such as tannin, phytate, sinapine, crude fibre etc. Presence of these antinutrients limits the use and marketing of rapeseed meals and a significant amount of it goes unused and ends up as waste. We investigated the genetic architecture of crude protein, methionine, tryptophan, total phenols, β-carotene, glucosinolates (GLS), phytate, tannins, sinapine, and crude fibre content of defatted seed meal samples by conducting a genome-wide association studies (GWAS), using a diversity panel comprising 96 Brassica napus genotypes. Genotyping by sequencing (GBS) was used to identify 77,889 SNPs, spread over 19 chromosomes. Genetic diversity and phenotypic variations were generally high for the studied traits. Eleven promising genotypes were identified which showed high protein quality, high antioxidants and lower amount of antinutrients. A significant negative correlation between protein and limiting amino acids and a significant positive correlation between GLS and phytic acid were observed. General and mixed linear model were used to estimate the association between the SNP markers and the seed quality traits and quantile-quantile (QQ) plots were generated to allow the best fit algorithm. Annotation of genomic regions around associated SNPs helped to predict various trait related candidates such as ASP2 and EMB1027 (amino acid biosynthesis); HEMA2, GLU1 and PGM (tryptophan biosynthesis); MS3, CYSD1 and MTO1 (methionine biosynthesis); LYC (β-carotene biosynthesis); HDR and ISPF (MEP pathway); COS1 (riboflavin synthesis); UGT (phenolics biosynthesis); NAC073 (cellulose and hemi-cellulose biosynthesis); CYT1 (cellulose biosynthesis); BGLU45 and BGLU46 (lignin biosynthesis); SOT12 and UGT88A1 (flavonoid pathway) and; CYP79A2, DIN2 and GSTT2 (GLS metabolism) etc. The functional validation of these candidate genes could confirm key seed meal quality genes for germplasm enhancement programmes directed at improving protein quality and reducing the antinutritional components in B. napus.